Evaluasi Manajemen Risiko Produk Musyarakah dalam Meminimalisir Risiko Pembiayaan Bagi Hasil - Vio Daniswan (FAI, 2017)
Evaluasi Manajemen Risiko Produk Musyarakah dalam Meminimalisir Risiko Pembiayaan Bagi Hasil